PENGARUH PELATIHAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT BANK CENTRAL ASIA KCU RAWAMANGUN - Dewi Arianti; Nuridin (Jurnal Ekonomi dan Industri, 2023)
This research aimed to find out and examine the effect of job training and work environment on the performance of employees of PT Bank Central Asia KCU Rawamangun simultaneously and partially. This research using quantitative research methods with causality research design. The sampling technique in this study used a saturated sample. Data collection was carried out by distributing questionnaires to employees of PT Bank Central Asia KCU Rawamangun. Data analysis techniques using simultaneous and partial linear regression analysis. The results of this study indicate that job training and work environment variables have a positive effect on employee performance simultaneously, job training has a positive effect on employee performance partially, and the work environment has a positive effect on employee performance partially.